1998
DOI: 10.1136/bmj.316.7138.1138
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of cost effectiveness of guided self management and traditional treatment of asthma in Finland

Abstract: Objective: To evaluate the READER model for critical reading by comparing it with a free appraisal, and to explore what factors influence different components of the model. Design: A randomised controlled trial in which two groups of general practitioners assessed three papers from the general practice section of the BMJ. Setting: Northern Ireland. Subjects: 243 general practitioners. Main outcome measures: Scores given using the READER model (Relevance, Education, Applicability, Discrimination, overall Evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 3 publications
1
29
0
1
Order By: Relevance
“…Finally, in an intervention that emphasized peak fl ow monitoring, Lahdensuo et al found that patients with the intervention had signifi cantly fewer direct medical costs, fewer unscheduled outpatient visits, and fewer work days missed because of asthma-related illness, as well as a signifi cantly better quality of life. 25,26 Overall, our fi ndings on process of care are similar to the fi ndings obtained for the pediatric population in the same study. 27 For the pediatric population more effects were signifi cant because the sample sizes were larger.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, in an intervention that emphasized peak fl ow monitoring, Lahdensuo et al found that patients with the intervention had signifi cantly fewer direct medical costs, fewer unscheduled outpatient visits, and fewer work days missed because of asthma-related illness, as well as a signifi cantly better quality of life. 25,26 Overall, our fi ndings on process of care are similar to the fi ndings obtained for the pediatric population in the same study. 27 For the pediatric population more effects were signifi cant because the sample sizes were larger.…”
Section: Discussionsupporting
confidence: 78%
“…In the mid-1990s, early randomised studies showed that guided self-management with patients' own adjustment of anti-inflammatory medication based on symptoms and home peak flow measurements reduced exacerbations and other asthma events compared with traditional therapy [72]. This also resulted in reduced asthma care costs [73]. A systematic review of 36 trials found guided self-management of asthma in adults to be clearly advantageous compared with usual care and to significantly improve patients' health [74].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such a system has the potential to improve patients' compliance to treatment. Guided management of allergic diseases including asthma was found to be effective (46,47) with clear evidence provided by the Finnish Asthma Programme (48) and the Allergy Programme (49,50).…”
Section: Continuous Management Of Symptoms During Allergen Exposurementioning
confidence: 99%